SAGITTAL AND VERTICAL CHARACTERISTICS OF DENTAL ARCH IN BOYS AND GIRLS WITH ORTHOGNATHIC BITE DEPENDING ON THE SHAPE OF HEAD AND TYPE FACE - Глушак, А.А. (World of Medicine and Biology, 2015)
In boys and girls of Podillya with orthognathic bite identified boundary percentile scope values sagittal and vertical characteristics of the dental arch in representatives with different form of head and face. Installed differences sagittal and vertical characteristics of the dental arch between the representatives with different shape of the head (only for girls vertical size of the arc) and different types of face: in boys - for vertical size of the arc (mainly at the level of canine and first large and small molar teeth); in girls - for the depth of the palate at the level of canines. Significant differences sagittal dental arch characteristics of boys and girls in the allocation to different craniotypes and different types of face practically not installed. In boys and girls practically not found significant sex differences of size sagittal and vertical characteristics of the dental arch.
Keywords: adolescents; face type; orthognathic bite; characteristics of dental arch; sex differences